Some Preliminary Considerations for the Legal-Economic Analysis of Corporate Social Responsibility - Méndez Reátegui, Rubén; Tabra Ochoa, Edison (Ius Humani. Jornal do direito, 2021)
This review article presents some preliminary considerations and describes the evolution of corporate social responsibility, which is necessary for an informed study of this " tool". In that sense, the authors resort to a preliminary exploration of the conceptual framework of the legal-economic approach presenting social responsibility and the relationship that subsists with " property rights", the relevance of " transaction costs", among other aspects. They also explore the interrelation between social responsibility and its forms of legal exercise and its characterization in areas that involve linking it with workers, unions, and consumers. The aim is to highlight its importance and build a contribution where social responsibility will be studied from an analytical and empirical perspective. Thus, it is sought to conclude that the company considers implementing and complying with good corporate governance standards since they expand the shared vision of business management, effectively allocating resources to obtain the most significant benefits of establishing a corporate social responsibility regime.